Work-Family Conflict and Career Satisfaction of Employees in The Banking Industry of Ghana: The Role of Spiritual Intelligence - Essandoh, Emmanuel; Ofori Appiah, Salomey; Tetteh Kwao, Isaac; Amfo-Antiri, Dorothy (Manunggal Halim Jaya, 2023)
The study empirically examined the role of spiritual intelligence in the nexus between work-family conflict and employees’ career satisfaction in the banking industry of Ghana. Design, methodology/approach-Given the reliance on explanatory research design, the study utilized structured questionnaire for gathering the primary data quantitatively from 335 randomly selected participants. A second-order model was configured in SMART PLS for testing of the directional hypotheses formulated. Findings- Both family-to-work and work-to-family conflict account for significant changes in employee career satisfaction. Also, the moderation analysis showed that spiritual intelligence brought variance into the model and had a small but significant positive effect on the relationship between work-to-family conflict and career satisfaction. The second effect of spiritual intelligence also brought variance into the model and had a small but significant negative effect on the relation between family-to-work and career satisfaction. Research limitations- Rural banks and other financial institutions were not included in the study, hence limiting the generalization of the findings from this perspective. Practical implication- Management of banks in Ghana would be encouraged to take specific actions that are likely to reduce the conflict between work and family roles to help their employees achieve their career satisfaction. Again, spiritual intelligence can be taught and encouraged at the workplace to help mitigate the psychological disorder created because of work-family conflict. Originality/value-Empirically, this study is the first of its kind that has sought to shed light on an understanding of the moderating effect spiritual intelligence on the nexus between work-family conflict and employees' career satisfaction in the Ghanaian banking sector the in Sub-Saharan country-context.